"We Will Never Yield" : Jews, the German Press, and the Fight for Inclusion in the 1840s - Meola, David A. (Book collections on Project MUSE., 2023)
"How did German Jews present their claims for equality to everyday Germans in the first half of the nineteenth century? We Will Never Yield offers the first English-language study of the role of the German press in the fight for Jewish agency and participation during the 1840s. David Meola explores how the German press became a key venue for public debates over Jewish emancipation; religious, educational, and occupational reforms; and the role of Jews in German civil society, even against a background of escalating violence against the Jews in Germany, We Will Never Yield sheds light on the struggle for equality by German Jews in the 1840s and demonstrates the value of this type of archival source of Jewish voices that has been previously underappreciated by historians of Jewish history"--